Penerapan Sistem Akuntansi Keuangan Pemerintah Daerah Dan Sistem Pengendalian Internal Terhadap Kualitas Laporan Keuangan Pemerintah Daerah - ALIF FARUQI FEBRI YANTO (Fakultas Ilmu Sosial Dan Politik, Universitas Wijayakusuma Purwokerto, 2023)
This research aims to determine the influence of the Regional Financial Accounting System and Internal Control System on the Quality of Regional Government Financial Reports. This research uses a purposive sampling technique, the sample from this research was obtained from 47 financial employees of the Pasuruan district government. The analytical method for this research uses multiple linear regression analysis using the analysis tool, namely SPSS version 25. The results of the research show that the Regional Financial Accounting System variable influences the Positive Quality of Regional Government Financial Reports, Internal Control System has a positive effect on the Quality of Regional Government Financial Reports. Keywords; Financial Accounting System, Internal control system, quality of financial reports